Community Perspectives on Psychological Assessment Reports for Autistic Young Adults - Garagozzo, Ariana; Aziz, Ardhika; Kaplan-Kahn, Elizabeth A.; Yerys, Benjamin E. (Journal of autism and developmental disorders, 2024)
Clinicians rarely solicit community feedback on psychological assessment reports. This study addresses this knowledge gap to: (1) improve the usefulness of reports for patients and families, (2) increase access to needed services, and (3) make reports accessible for autistic people and their families. An autistic researcher and a non-autistic researcher jointly conducted qualitative interviews with autistic young adults, caregivers, and a service provider. Participants read a de-identified psychological assessment report about an autistic young adult with intellectual disability seeking resources for his transition to adulthood. Participants provided feedback about (1) how easy the report was to read, (2) how useful the report seemed, and (3) perceptions of language (i.e., empowering/offensive/neutral). Autistic young adults, caregivers, and the service provider all expressed a desire for short and clear reports in bulleted format. Caregivers stressed the importance of (1) using simple language to describe diagnostic testing and (2) including comprehensive resources, and autistic young adults expressed the importance of (1) including information about daily routines, habits, and interests and (2) giving patients' long-term goals the same consideration as caregivers' long-term goals. We highlight that standard psychological assessment reports have not effectively met the needs of autistic people and family members. Autistic people and caregivers prefer brief reports written in plain language that include more information about the patients' interests, routines, and preferences and less detailed information about psychological tests. Our findings identify ways to improve the usefulness and readability of psychological assessment reports for autistic people.